CD4+ DAN CD8+ INTERFERON GAMMA TUBERKULOSIS PARU AKTIF DAN TUBERKULOSIS LATEN - Betty Agustina Tambunan; John Wiwin; Jusak Nugraha; Soedarsono Soedarsono (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2016)
Tuberculosis (TB) is a global health problem. Immune response through CD4+ T cells and CD8+T cells is needed to produce Interferongamma (IFN-γ). IFN-gamma is a cytokine that can kill Mycobacterium tuberculosis. Not all individuals will lead to illness or activediseases. The aim of this study was to know the cellular immune response like IFN-gamma expression of T-CD4+ cells and CD8+ cellsbetween active TB with latent TB. The design of the study was cross sectional obervational in a population suffering from active andlatent TB. The subjects consisted of 11 (eleven) active TB patients and 10 (ten) latent TB patients from the Special Pulmonary Hospitaland the Dr Soetomo Hospital, Surabaya. The examination of interferon gamma expression of CD4+ and CD8+ was by Flowcytometrymethod. These results were analyzed by Student t test or Mann-Whitney test. The mean CD4+ percentage of active TB (28.75%) waslower than the latent one (TB) (33.21%) but no significant difference (P value=0.114) was shown. The mean CD8+ percentage ofactive TB (30.46%) was higher than the latent one (TB) (28.87%) but no significant difference (P value=0.481) was found. Themean CD4+IFN-γ percentage of active TB (2.51%) was higher than latent one (TB) (1.10%) and there was a significant difference(P value=0.014). The mean CD8+IFN-γ percentage of active TB (2.91%) was lower than latent one (TB) (4.41%) and there was asignificant difference (P value=0.006). Based on this study, it can be concluded that the mean CD4+IFN-γ percentage of active TB washigher than latent TB and there was a significant difference. The mean of CD8+IFN-γ percentage of latent TB was higher than the activeone (TB). This suggested that CD8+ has a dominant part in latent TB and may be caused by the role of other cytokines, or genetics,nutrition, and body mass index factors.